UJI VALIDASI METODE SPEKTROFOTOMETRI ULTRAVIOLET PADA PENETAPAN KADAR TABLET KAPTOPRIL GENERIK DAN NAMA DAGANG - Marpaung, Jon Kenedy; Harun, Fatur Rahman; Girsang, Febriyantu (Jurnal Farmanesia, 2020)
In the manufacture of drugs, checking the levels of active substances is a requirement that must be met to ensure the quality of drug preparations. Good quality drug preparations will support the achievement of the desired therapeutic effect. One of the requirements for drug quality is that the content contained must meet the level requirements as stated in the Indonesian Pharmacopoeia, which is not less than 90% and not more than 110%. This study aims to test the validation of the ultraviolet spectrophotometric method on the determination of generic captopril tablets and trade names. The sample used consisted of 3 generic tablet preparations and 2 trade names. Determination of the concentration of captopril tablets in tablet preparations was carried out by ultraviolet spectrophotometry using 0.1N NaOH solvent at a wavelength of 236.2 nm and this validation test was carried out using the standard addition method. Parameters of the method validation test include accuracy (accuracy), precision (accuracy), limit of detection (Limit of Detection), and limit of quantitation (Limit of Quantitation). This method provides good determination and accuracy, LOD (Limit Of Detection) 0.575486 mcg/ml & LOQ (Limit Of Quantitation) 1.9179 mcg/ml is declared valid. The results of the validation test, obtained an average recovery value of 100.6% with an RSD value of 1.05%. Based on the research, the levels of captopril brand A tablets were 97.47 -+ 2.3670, captopril brand B tablets were 98.08 -+ 2.4911, captopril brand C tablets were 98.03 -+ 2.4223, captopril brand D tablets were 98.93 -+ 1.5138, captopril brand E tablets of 99.57 -+ 2.3985.